Synthesis and characterization of hydrogels from 1-vinylimidazole. Highly resistant co-polymers with synergistic effect - Primo, Gastón A. (2015)
Monomers N, N-(dimethyl) amine ethyl methacrylate (DMAEMT) and N-[3 - (dimethylamine) propyl] methacrylamide (DMAPMD) were co-polymerized with 1-vinylimidazole (VI) in different proportions and crosslinked with N,N′-methylenebisacrylamide (BIS) in aqueous phase, to yield highly resistant hydrogels. The polymeric products were studied by swelling kinetics, solvent diffusion within the crosslinked network, thermal decomposition, infrared spectroscopy (FTIR), variable pressure scanning electron microscopy (VP-SEM), and mechanical and rheological tests. The incorporation of VI in the polymerization reaction led to beneficial changes in the properties of the final materials such as improvement in the resistance of the materials and increase in the percentage of deformation capable of withstanding elongation before breaking. All VI-containing products were mechanically strong with respect to homo-polymers (DMAPMD 100% and DMAEMT 100%). The most resistant products were DMAPMD-co-VI 60% and DMAEMT-co-VI 60%. A synergistic effect with the addition of VI is revealed by Young's modulus that increases 5 and 10 times regarding the hydrogels yielded from pure monomers, respectively.